Empowering Islamic Hospitality: Designing A Halal Tourism Information System for Muslim Travelers in Bali, Indonesia - Yordan Yasin; Dana Indra Sensuse; Deden Sumirat Hidayat; Erisvaha Kiki Purwaningsih; Rika Ekawati (Eduvest - Journal of Universal Studies, 2024)
Indonesia has great potential as a halal tourism destination, and based on the 2023 Global Muslim Index, Indonesia is ranked first as a halal tourism destination. Bali, as one of the favorite tourist destinations in Indonesia, is, of course, also attractive for Muslim travelers. Unfortunately, there is still limited information regarding various Muslim Friendly tourist attractions and facilities there. The existing halal tourism information system also still has a low rating. This study uses a prototyping approach to design a halal tourism information system that is easy to use and access, especially for halal tourism in Bali. The prototype tested with the usability test obtained an average value of 3.9 on a 5 scale and got a higher score of 4.3 on ease of use and application expectations. The score shows that the system fulfilled its proposal to create an information system for halal tourism in Bali, Indonesia, which is easy to access and use.